Policy Implementation of the 2026 Senior High School Student Admission System in West Java, Indonesia - Ade Setiadi; Didin Muhafidin (GoAcademica Research & Publishing, 2026)
The 2026 reform of Indonesia's senior high school student admission system marked a transition from the zoning mechanism to a domicile-based approach intended to enhance transparency, fairness, and equitable access to public education. As the province with the largest secondary school population in Indonesia, West Java provides an important setting for examining how this policy is implemented in practice. This study aims to analyze the implementation of the 2026 Senior High School Student Admission Policy in West Java, identify the institutional challenges and adaptive responses that emerged during implementation, and explore its implications for educational equity. This study employed a qualitative multiple case study design. Data were collected through in-depth interviews with education officials, school principals, admission committee members, parents, and students, supported by observations and document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while Edward III's policy implementation framework and the educational equity perspective guided the analysis. The findings reveal that the policy implementation has strengthened transparency and expanded access through multiple admission pathways. However, several challenges persist, including uneven public understanding of domicile provisions, disparities in digital infrastructure and administrative capacity, and persistent perceptions regarding differences in school quality. Although the transition to domicile-based admissions has improved perceptions of procedural fairness and widened opportunities for disadvantaged students through affirmative pathways, structural inequalities among public schools continue to hinder the achievement of substantive educational equity. This study contributes to the literature by providing one of the earliest empirical analyses of Indonesia's 2026 student admission reform and demonstrating how policy implementation processes shape educational equity outcomes within a decentralized education system.